Development of an audio evoked resoponse system to facilitate anaesthesia monitoring - Noor, Shabnam; Hossain, Saida (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.